Alendronate-functionalized double network hydrogel scaffolds for effective osteogenesis - Tang, Guoke; Zhu, Liang; Wang, Weiheng; Zuo, Dongqing; Shi, Changgui; Yu, Xiaojie; Chen, Rui (Frontiers in Chemistry, 2022)
Development of artificial bone substitutes mimicking the extracellular matrix is a promising strategy for bone repair and regeneration. In views of the actual requirement of biomechanics, biodegradability, and bioactivity, herein, a double-network (DN) hydrogel was constructed by interspersing a methacrylated gelatin (GelMA) network into alendronate (ALN)-modified oxidized alginate (OSA) network via Schiff base reaction and photo-crosslinking process to promote in situ bone regeneration. This GelMA@OSA-ALN DN hydrogel possessed favorable network and pores, good biocompatibility, and enhanced biomechanics. Notably, the introduction of Schiff base furnished the ND hydrogel scaffold with pH-responsive biodegradation and sustained ALN drug release delivery, which could provide effective bioactivity, upregulate osteogenesis-related genes, and promote the cell viability, growth, proliferation, and osteogenesis differentiation for bone regeneration. Therefore, we provide a new insight to develop functional DN hydrogel scaffold toward governing the on-demand drug release and achieving the stem cell therapy, which will be developed into the minimally invasive gelling system to prolong local delivery of bisphosphonates for the bone-related diseases.